2012
DOI: 10.1002/jbm.a.34480
|View full text |Cite
|
Sign up to set email alerts
|

Nanopatterning effects on astrocyte reactivity

Abstract: An array of design strategies have been targeted toward minimizing failure of implanted microelectrodes by minimizing the chronic glial scar around the microelectrode under chronic conditions. Current approaches toward inhibiting the initiation of glial scarring range from altering the geometry, roughness, size, shape, and materials of the device. Studies have shown materials which mimic the nanotopography of the natural environment in vivo will consequently result in an improved biocompatible response. Nanofa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 51 publications
1
45
1
Order By: Relevance
“…Prepared films and fiber scaffolds were then plasma treated for 90 seconds using a Plasma Cleaner (Harrick Plasma, Ithaca, NY). Components within the extracellular matrix (ECM) are known to regulate astrocyte behavior [4142]. In order to determine the best ECM coating for the PLLA fibers that promoted robust astrocyte adhesion, astrocytes were seeded on aligned PLLA fibers that were coated overnight with fibronectin (Sigma-Aldrich), laminin (Invitrogen), or collagen I (Invitrogen) at a concentration of 10 µg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Prepared films and fiber scaffolds were then plasma treated for 90 seconds using a Plasma Cleaner (Harrick Plasma, Ithaca, NY). Components within the extracellular matrix (ECM) are known to regulate astrocyte behavior [4142]. In order to determine the best ECM coating for the PLLA fibers that promoted robust astrocyte adhesion, astrocytes were seeded on aligned PLLA fibers that were coated overnight with fibronectin (Sigma-Aldrich), laminin (Invitrogen), or collagen I (Invitrogen) at a concentration of 10 µg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…1 Properties such as the stiffness and topography of the scaffold material have a significant effect on the number of primary neurons and astrocytes attached, as well as on the direction of their outgrowths. [2][3][4] Researchers have been working on micro-or nanopatterned substrates to guide neuronal outgrowth, to help study the neural electrical signal transmission in single neurons, 5 and to aid nerve regeneration processes. 6 Therefore, our goal is to combine microfluidics with tissue engineering to create a "living brain," generating realistic in vitro neural circuitry, which can be used to standardize experimental neuronal cell culture.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous reports that the introduction of FBG into the CNS after injury triggers CSPG production [46], and that fact that AGG already contains inhibitory CS chains, it appears that the alignment itself was the dominant contributing factor resulting in the decrease in CSPG expression seen here (Fig 5). It has been shown that the presence of topographical cues that aligned astrocytes also reduced astrocyte reactivity [47]. Similarly, astrocytes grown on aligned electrospun fibers of polycaprolactone had decreased GFAP expression compared to those on random fibers [48].…”
Section: Discussionmentioning
confidence: 99%